(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2022)
India is the 6th largest economy of the world. As per the data 49% of manpower is employed in farming, where as the farming sector contribution to the GDP is merely 16%. This is because of two main causes one is the disguised employment in the farming sector. The second reason being India’s large portion of farming activities depend upon the monsoon. The changing weather pattern makes the corps production vulnerable. The security of crops can be provided by providing cost effective and continuous irrigation facilities, which will not only eliminate the dependency on the weather also help farmers to boost their economy by increasing the crops production. This might help to increase the socio-economic condition of the farmers. In this study, standalone solar PV is introduced and examined for the said reason. This technology involving renewable energy provides a novel solution for the challenging task because during sunny hour maximum water needs to irrigate the field, and during rainy season the water requirement is null or less. During both the seasons the model can work effectively, to provide cost effective and eco-friendly energy supply. The system is modeled and analyzed through HOMER.